Toleransi di Era Kontemporer: Kajian Pemikiran Ahmad Syarif Yahya untuk Membangun Harmoni Antar Agama - Abdullah, Muqni Affan; Irhamna, T. Muhammad (Prodi Studi Agama-Agama, 2023)
This research examines the thoughts of Ahmad Syarif Yahya as outlined in his works